2004
DOI: 10.1038/sj.bjc.6601579
|View full text |Cite
|
Sign up to set email alerts
|

Phase I study to determine the safety, tolerability and immunostimulatory activity of thalidomide analogue CC-5013 in patients with metastatic malignant melanoma and other advanced cancers

Abstract: We assessed the safety, tolerability and efficacy of the immunomodulatory drug, CC-5013 (REVIMIDt), in the treatment of patients with metastatic malignant melanoma and other advanced cancers. A total of 20 heavily pretreated patients received a dose-escalating regimen of oral CC-5013. Maximal tolerated dose, toxicity and clinical responses were evaluated and analysis of peripheral T-cell surface markers and serum for cytokines and proangiogenic factors were performed. CC-5013 was well tolerated. In all, 87% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
84
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(90 citation statements)
references
References 39 publications
5
84
0
1
Order By: Relevance
“…There remains strong in vitro evidence that conventional T cells show a Th1 cytokine bias when cultured with thalidomide analogues, 49,50 and along with others, we report similar findings for NKT cells cultured with lenalidomide. [29][30][31] There is also evidence that lenalidomide can enhance the activation of conventional T cells in vivo, 16,22,51 but most studies, including our own, suggest lenalidomide's in vitro effects on NKT cells are co-stimulatory, and would therefore require an additional activation signalFsuch as that provided by aGalCer in in vitro assays. Hence, NKT cell activity may be augmented by lenalidomide if the NKT cells were independently activated through coadministration of aGalCer, or endogenously by selfagonist glycolipids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There remains strong in vitro evidence that conventional T cells show a Th1 cytokine bias when cultured with thalidomide analogues, 49,50 and along with others, we report similar findings for NKT cells cultured with lenalidomide. [29][30][31] There is also evidence that lenalidomide can enhance the activation of conventional T cells in vivo, 16,22,51 but most studies, including our own, suggest lenalidomide's in vitro effects on NKT cells are co-stimulatory, and would therefore require an additional activation signalFsuch as that provided by aGalCer in in vitro assays. Hence, NKT cell activity may be augmented by lenalidomide if the NKT cells were independently activated through coadministration of aGalCer, or endogenously by selfagonist glycolipids.…”
Section: Discussionmentioning
confidence: 99%
“…17,19,20 Lenalidomide's mode of action in MDS is not well understood, but its proposed biological effects include inhibition of angiogenesis, promotion of erythroid hemoglobin production and acceleration of apoptotic death of abnormal hematopoietic progenitors, 16,17,21 and it is also reported to have immunoregulatory activity through modulation of natural killer cell, monocyte and dendritic cell function, inhibition of FOXP3 þ T regulatory cells and costimulation of T cells leading to increased proliferation and interferon-g (IFN-g) production. 16,[22][23][24] Interestingly, many of these immunological activities have been attributed in other settings to the prodigious cytokine production of NKT cells. [2][3][4]25 A causative link has not been established between NKT cell defects and the development of MDS, but disordered NKT cell function has been reported for patients with MDS, [10][11][12] and is clearly implicated in the control or progression of a wide range of tumors.…”
Section: Introductionmentioning
confidence: 99%
“…The first published study of lenalidomide in patients with solid tumours suggests that lenalidomide has limited clinical activity in patients with advanced and heavily pretreated metastatic malignant melanoma and other solid cancers (Bartlett et al, 2004b). The primary objective of this phase I study was to assess the safety and tolerability of lenalidomide and in this regard there were no serious adverse effects attributed to treatment.…”
Section: Imids In Solid Tumoursmentioning
confidence: 99%
“…Lenalidomide is an immune modulating drug that activates T cells to secrete IL-2, which in turn activates NK cell cytotoxicity and ADCC [97,98]. Clinical trials in children and adults demonstrated increased numbers of NK cells and cytotoxicity, decreased T regulatory cells, and increased secretion of IL-2, IL-15, and GM-CSF after 21 days of lenalidomide treatment [99,100]. Thus, lenalidomide may be useful for activating NK cells to enhance mAb immunotherapy of neuroblastoma.…”
Section: B Natural Killer Cellsmentioning
confidence: 99%